(untitled) (London Journal of Engineering Research, 2023)
Poly ionic liquidwas introduced as aqueous two-phase extraction (ATPE) sorbent accompanied with UV spectrophotometry for Allura red (AR) separation in food samples. Different parameters, like pH value, adsorption temperature and time , were studied. the preconcentration factor for AR was 27. The linear range, detection limit (DL), correlation coefficient (R) and relative standard deviation (RSD) were found to be 0.10-9.00 ?g/mL, 5.2 ?g/L, 0.9987 and 3.10% (n=3, c=4.00 ?g/mL).This method was successfully applied for separation / analysis of allura red pigment in food samples with satisfactory results.